Comparative study on the water quality of growth of GIFT (Genetically Improved Farmed Tilapia) strain (Oreochromis niloticus L.) in re-circulatory and static systems - Ali, MS; Amin, MR; Khaleque, MA; Amin, MR; Alam, MT; Babul, MBH (University Journal of Zoology, Rajshahi University, 2007)
Key words: Water quality; growth; GIFT strain; re-circulating and static systems Univ. j. zool. Rajshahi Univ. Vol.22, 2003. pp. 55-62